Service function chain deployment algorithm based on optimal weighted graph matching - Dan LI; Julong LAN; Peng WANG; Yuxiang HU (Tongxin xuebao)
Service function chain can support flexible network service requirement by linking virtual network functions.Aiming at the problem of service function chain deployment in a resource-constrained network,an algorithm for service function chain deployment based on optimal weighted graph matching was proposed.The service function chains was composed into graphs of functional topography,and the optimal matching results between graphs of functional topology and physical topology was obtained using eigendecomposition approach,and furtherly the matching results by hill-climbing method was optimized.Simulation results show that,the proposed algorithm can reduce the required bandwidth to deploy service function chains,balance the load of nodes and bandwidth of links,and support more service requests.What is more,the algorithm has a lower computation complexity and higher time efficience.